2011
DOI: 10.1186/1757-2215-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear survivin expression is a positive prognostic factor in taxane-platinum-treated ovarian cancer patients

Abstract: BackgroundSurvivin is an inhibitor of apoptosis and a regulator of mitotic progression. TP53 protein is a negative transcriptional regulator of survivin. The aim of our study was to evaluate the clinical significance of survivin expression in advanced stages ovarian cancer with respect to the TP53 status.MethodsSurvivin and TP53 expression was evaluated immunohistochemically in 435 archival samples of ovarian carcinomas (244 patients were treated with platinum/cyclophosphamide-PC/PAC; 191-with taxane-platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…No independent predictive and prognostic significance of survivin was observed in the group without p53 protein expression. 15 In our study, which assessed selected proteins of apoptosis, we found that high expression of survivin was a favorable prognostic factor in patients with AOC treated with NAC. As in the study by the Polish Ovarian Cancer Group, the effect was more significant in the group of patients with positive expression of p53.…”
Section: Association Between Survivin Expression and Osmentioning
confidence: 68%
“…No independent predictive and prognostic significance of survivin was observed in the group without p53 protein expression. 15 In our study, which assessed selected proteins of apoptosis, we found that high expression of survivin was a favorable prognostic factor in patients with AOC treated with NAC. As in the study by the Polish Ovarian Cancer Group, the effect was more significant in the group of patients with positive expression of p53.…”
Section: Association Between Survivin Expression and Osmentioning
confidence: 68%
“…They also observed that TP53 status determines the clinical importance of nuclear survivin expression in taxane-platinum treated ovarian cancer patients (Felisiak-Golabek et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In the last years, the retrospective analysis of patient specimens and xenografts tumor data are pointing out that there is a clear connection between the existence of high levels of survivin protein and the resistance to therapy and poor prognosis in multiple tumor types (1922). In the particular case of ovarian cancer, the prognostic role of survivin is not clear due to some conflicting results (2326). However, the potential of survivin as a target for apoptosis-based therapy is well-established (27).…”
Section: Discussionmentioning
confidence: 99%